Contribución al conocimiento de la flora extremeña (España). - Vázquez Pardo, Francisco M.; Ramos Maqueda, Soledad; Lucas Pimienta, Ana Belén; Blanco Salas, José; García Torres, Susana (Acta Botanica Malacitana, 2003)
New floristic records for Valladolid province. II Palabras clave. Corología, flora vascular, España, Valladolid. Key words. Chorology, vascular flora, Spain, Valladolid.